2005
DOI: 10.1074/jbc.m406037200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Cooperative Mechanism Involving Interleukin-13 and Eotaxin-2 in Experimental Allergic Lung Inflammation

Abstract: Pulmonary eosinophilia, a hallmark pathologic feature of allergic lung disease, is regulated by interleukin-13 (IL-13) as well as the eotaxin chemokines, but the specific role of these cytokines and their cooperative interaction are only partially understood. First, we elucidated the essential role of IL-13 in the induction of the eotaxins by comparing IL-13 gene-targeted mice with wild type control mice by using an ovalbumin-induced model of allergic airway inflammation. Notably, ovalbumin-induced expressions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
124
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(137 citation statements)
references
References 67 publications
10
124
1
2
Order By: Relevance
“…It is interesting to note that in that model, the relative level of eosinophils in the lung of eotaxin-1-deficient mice was increased compared with wild-type mice. 32 Our current study describes a mechanism by which airway eosinophilia is regulated by localized expression of the eotaxin chemokines. Notably, CCR3 was required for both airway and peribronchial eosinophilia in our transgenic mice, demonstrating a cooperative mechanism for CCR3 and its ligands in directing the recruitment and localization of pulmonary eosinophils.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is interesting to note that in that model, the relative level of eosinophils in the lung of eotaxin-1-deficient mice was increased compared with wild-type mice. 32 Our current study describes a mechanism by which airway eosinophilia is regulated by localized expression of the eotaxin chemokines. Notably, CCR3 was required for both airway and peribronchial eosinophilia in our transgenic mice, demonstrating a cooperative mechanism for CCR3 and its ligands in directing the recruitment and localization of pulmonary eosinophils.…”
Section: Discussionmentioning
confidence: 95%
“…[27][28][29] Activated eosinophils have been shown to be a source of several molecules implicated in tissue remodeling processes, including IL-13-induced transforming growth factor (TGF)-␤ 1 . 30,31 Prior studies have shown that IL-13-induced eosinophil recruitment in the lung airway and lung tissue in an acute model are regulated by eotaxin-2 and eotaxin-1, respectively, 32 but the role of these molecules in regulating other aspects of IL-13-induced pathology has not been addressed.…”
mentioning
confidence: 99%
“…These results are consistent with previously reported acute models of IL-13-induced airway inflammation (1-4). Administration of IL-13 also induced expression of the mucin gene MUC5AC (2,(34)(35)(36) (Fig. 1C) and increased goblet cell mucus production (assessed by periodic acid-Schiff staining; data not shown).…”
Section: Intranasal Delivery Of Ril-13 Induces Ahr Airway Inflammatimentioning
confidence: 86%
“…The mouse genome was shown to only contain functional eotaxin-1 and eotaxin-2 [59,60]. Under baseline conditions, eotaxin-1 and eotaxin-2 are constitutively expressed in a variety of tissues, with especially high levels in the gastrointestinal tract and thymus [47,60,61].…”
Section: Migration Of Eosinophils Into the Intestinementioning
confidence: 99%